Association between serum carotenoids levels and endometriosis risk: evidence from the National Health and Nutrition Examination Survey - Huang, Jian (Frontiers in Nutrition, 2025)
BackgroundThe relationship between serum levels of carotenoids and endometriosis remains largely unknown. The aim of this study is to assess the association between serum levels of major carotenoids (α-carotene, β-carotene, β-cryptoxanthin, lutein/zeaxanthin, and trans-lycopene) and the risk of endometriosis in US women.MethodsThe data were obtained from the 2001–2006 National Health and Nutrition Examination Surveys (NHANES), which included a total of 3,636 women aged 20 to 54. Serum levels of α-carotene, β-carotene, β-cryptoxanthin, lutein/zeaxanthin, and trans-lycopene were measured using high performance liquid chromatography (HPLC) with photodiode array detection. Endometriosis was defined as self-report. Weighted multivariate logistic regression analyses were conducted to evaluate the associations of the serum levels of the major carotenoids with endometriosis risk. Additionally, restricted cubic spline (RCS) was employed to assess the possibility of nonlinear associations. Finally, subgroup analyses were utilized to estimate the influence of several covariates on the associations.ResultsWeighted multivariate logistic regression analyses showed that, after adjusting for all covariates taken into account, there was a significant association between serum lutein/zeaxanthin levels and reduced risk of endometriosis (Quartile 3 vs. Quartile 1: odds ratio [OR] = 0.62, 95% confidence interval [CI]: 0.42–0.90; Quartile 4 vs. Quartile 1: OR = 0.54, 95% CI: 0.36–0.81, P for trend = 0.001). However, no significant associations of serum levels of other carotenoids with endometriosis were found in multivariable-adjusted models that included all covariates. RCS analysis did not reveal any non-linear relationships. Subgroup analyses indicated that the inverse association between serum lutein/zeaxanthin levels and reduced endometriosis risk was significant only in individuals under 40 years of age, in both White and non-White populations, in smokers, and among those who had ever used oral contraceptives.ConclusionSerum lutein/zeaxanthin levels may offer protective effects against endometriosis in specific subpopulations. Further prospective research is necessary to validate these findings.